TABOO AVOIDANCES IN KARO LANGUAGE - Jumat Barus (Universitas Islam Sumatera Utara (UISU), 2020)
Civilized society like Karo knows taboo culture and how to avoid it well, so that they can be avoided from social conflict and can live peacefully. However, taboo in language and the way to avoid them are considered increasingly scarce as globalization develops among the current millennial generation. As an effort to provide an understanding about the matter concerned towards future generations, this study describes various ways of avoiding the three types of taboo in Karo: taboo in kinship, i.e. among bengkila and permain, turangku and turangku, and mami and kela; context-speciﬁc taboos, i.e. words derived from non-taboo words, and words related to social and physical defects; and general taboos, i.e. swearing and unmentionable words. This research was conducted using descriptive qualitative with ethnographic method. The data were obtained from the key informants who were from indigenous people of Tanah Karo Regency. It is found that taboos in kinship can be avoided by strategy of third-person intermediary, strategy of metaphor through object, and strategy of using the word nina. Context-specific taboo and general taboo can be avoided by various forms of euphemism. However, taboo of swearing type does not have form of refinement because of its purpose and function as emotive expression.